Respuesta :
Answer:
The inverse of f(x) is [tex]f ^ {- 1}(x) = x + 2[/tex]
Step-by-step explanation:
To find the inverse of the function [tex]f (x) = x-2[/tex], perform the following steps:
1) do [tex]y = f (x)[/tex]
[tex]y = x-2[/tex]
2) Solve the equation for the variable x.
[tex]y + 2 = x -2 +2[/tex]
[tex]y + 2 = x[/tex]
3) exchange the variable x with the variable y
[tex]y + 2 = x[/tex] ----> [tex]x + 2 = y[/tex]
4) Change the variable y by [tex]f ^{- 1}(x)[/tex]
Finally the inverse function is:
[tex]f ^ {- 1} (x) = x + 2[/tex]